2020
DOI: 10.1101/2020.03.27.010850
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating and integrating spatial capture-recapture models with data of variable individual identifiability

Abstract: Many applications in ecology depend on unbiased and precise estimates of animal population density. Spatial capture recapture models and their variants have become the preferred tool for estimating densities of carnivores. Within the spatial capture-recapture family are variants that require individual identification of all encounters (spatial capture-recapture), individual identification of a subset of a population (spatial mark-resight), or no individual identification (spatial count). In addition, these mod… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Although it is possible to simulate multiple types of animal movement in virtual landscapes, it is difficult to know which, if any, of the types accurately represent animals moving through real landscapes. Several empirical comparisons of unmarked methods exist and provide insight into the performance of multiple methods in common systems (Doran-Myers 2018;Burgar et al 2018;Ruprecht et al 2020). However, we suggest that further empirical comparisons would be valuable for identifying systems or conditions where abundance estimates from different methods diverge.…”
Section: Collection Of Ancillary Datamentioning
confidence: 89%
See 1 more Smart Citation
“…Although it is possible to simulate multiple types of animal movement in virtual landscapes, it is difficult to know which, if any, of the types accurately represent animals moving through real landscapes. Several empirical comparisons of unmarked methods exist and provide insight into the performance of multiple methods in common systems (Doran-Myers 2018;Burgar et al 2018;Ruprecht et al 2020). However, we suggest that further empirical comparisons would be valuable for identifying systems or conditions where abundance estimates from different methods diverge.…”
Section: Collection Of Ancillary Datamentioning
confidence: 89%
“…2018; Ruprecht et al. 2020). However, we suggest that further empirical comparisons would be valuable for identifying systems or conditions where abundance estimates from different methods diverge.…”
Section: Validating Methods Via Simulations and Empirical Comparisonsmentioning
confidence: 99%
“…4e) and in another instance, a GPS-collared cougar killed and consumed a GPS-collared coyote. By observing dead coyotes at 7% of cougar kill sites, and given a cougar density of 2.2 per 100 km 2 in our study area (22), this suggests that approximately 8.4 coyotes are killed per 100 km per year. With a coyote density of 33.9 per 100 km 2 (22), this level of mortality reflects 23.0% (95% CI: 8.4-54.5% when all sources of uncertainty are propagated) of coyotes killed by cougars annually:…”
Section: Resultsmentioning
confidence: 68%
“…We estimated that each cougar killed approximately 3.8 coyotes annually, though we note previous studies in the region have reported less coyote predation (21,37) so this value may partially be the result of a small sample size. Nonetheless, given a cougar density of 2.2 per 100 km 2 in our study area (22), this suggests that approximately 8.4 coyotes are killed per 100 km 2 per year. With a coyote density of 33.9 per 100 km 2 , this level of mortality reflects 23.0% (95% CI: 8.4-54.5% when all sources of uncertainty are propagated) of coyotes killed by cougars annually.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation